Heterobimetallic scandium–group 10 metal complexes with LM → Sc (LM = Ni, Pd, Pt) dative bonds. Issue 1 (3rd December 2019) - Cui, Peng; Xiong, Chunyan; Du, Jun; Huang, Zeming; Xie, Sijun; Wang, Hua; Zhou, Shuangliu; Fang, Huayi; Wang, Shaowu
Abstract : Heterobimetallic scandium–group 10 metal complexes featuring notable LM → Sc (LM = Ni, Pd, Pt) dative bonding interactions. Abstract : Heterobimetallic scandium complexes with whole group 10 metals were synthesized. All Sc–LM complexes were characterized by NMR spectroscopy, X-ray diffraction analysis and computational studies, which revealed notable LM → Sc (LM = Ni, Pd, Pt) dative bonding interactions in these heterobimetallic systems. Versatile coordination modes toward apical donors were observed in these heterobimetallic Sc–LM complexes, among which the Sc–Ni complexes 2 and 3 were reversibly bound to N2 and the Sc–Pt complex 5 was coordinated to an additional PPh3 ligand, while in the Sc–Pd complex 4 no apical donor was ligated.